Some problematic aspects of early termination - Sánchez Torres, Alexander Germán (2024)
This paper discusses the challenges faced by the aggrieved party or civil actor in the processes of early termination in the Peruvian criminal system.The mandatory intervention of the aggrieved party in the negotiation phase can affect the efficiency sought by negotiated justice, which drives the proposal to limit this preliminary phase to negotiations between the prosecutor and the defendant.The author suggests that the aggrieved party’s intervention should be restricted to the hearing addressing exclusively civil reparation, thereby ensuring their right to be heard without obstructing the criminal process. However, this restriction could raise questions about the effective judicial protection of the aggrieved party.Finally, the author concludes that greater autonomy in the initial negotiation, along with compensatory measures for the aggrieved party, would help balance expediency and justice in these processes, consolidating a more agile and equitable model of negotiated justice.